Tour de France in a digital television paradigm - Frandsen, Kirsten (MedieKultur: Journal of media and communication research, 2023)
This article analyses sports events as mega-events with global appeal and increasing socio-economic and cultural significance, and as genres which have now become important in the television industry’s transformation from broadcast to online streaming. It presents findings from a qualitative production analysis of how the Tour de France 2022 was shaped in a twofold strategic context. Genre specific aspects of the media event in the ongoing transformation of the television industry and wider strategic interests behind the hosting and organization of the start of the race in Denmark 2022 are discussed and their intertwinements are described. Based on interviews, documents, observations, screenshots and select broadcasts, the article presents a thematic analysis of how the event in Denmark was shaped in a shared concern for television’s ability to provide exposure of the race and the Danish context and public service broadcaster TV 2’s particular strategic branding interests in the event.